(untitled) (Ustozlar uchun, 2025)
The passive voice is often misunderstood and misused by some learners. The passive voice is a important tool in English grammar. It is said that some students get confused while forming a sentence with passive voice. Most of them have difficulties with tense use and grammatical structure.The overuse might lead to misunderstandings and indirect writing.Therefore, understanding its appropriate usage improves writing flexibility and the choices of style. This article will provide and explain educators with methods for effectively teaching the passive voice to English language learners.